Stereotyping of East Indian women in the Caribbean - Haniff, Nesha Z. (WAND St MichaelBB, 1996)
Examines why the stereotype of Indian Caribbean women persists by looking at the historical data, the role of violence in the Indian community, the impact of religion, the Indian family, the feminist movement in the Caribbean and the attitude of East Indian men.